2003
DOI: 10.1074/jbc.m300358200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the αvβ3 Integrin-interacting Motif of βig-h3 and Its Anti-angiogenic Effect

Abstract: ␤ig-h3 is an extracellular matrix protein that mediates adhesion and migration of several cell types through interaction with integrins. In the present study, we tested whether ␤ig-h3 mediates endothelial cell adhesion and migration, thereby regulating angiogenesis. In this study, we demonstrate that not only ␤ig-h3 itself but also all four fas-1 domains of ␤ig-h3 mediate endothelial cell adhesion and migration through interaction with the ␣ v ␤ 3 integrin. We found that the ␣ v ␤ 3 integrin-interacting motif … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 26 publications
2
108
2
Order By: Relevance
“…The four internal repeats region of Periostin share a homology with the axon guidance protein FAS1, containing sequences that allows binding of integrins and glycosaminoglycans in vivo (Elkins et al, 1990). FAS1 domains of big-h3, which shares a significant structural homology with Periostin, bear motifs interacting with integrins a3b1 and avb5 (Kim et al, 2000(Kim et al, , 2002 and mediate endothelial cell adhesion and migration via integrin avb3 (Nam et al, 2003). Similar to big-h3, we also previously found that interference with the function of integrins by specific anti-avb3 and anti-avb5 integrin antibodies had an effect on the ability of Periostin to mediate cell adhesion in OSCC cells (Kudo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The four internal repeats region of Periostin share a homology with the axon guidance protein FAS1, containing sequences that allows binding of integrins and glycosaminoglycans in vivo (Elkins et al, 1990). FAS1 domains of big-h3, which shares a significant structural homology with Periostin, bear motifs interacting with integrins a3b1 and avb5 (Kim et al, 2000(Kim et al, , 2002 and mediate endothelial cell adhesion and migration via integrin avb3 (Nam et al, 2003). Similar to big-h3, we also previously found that interference with the function of integrins by specific anti-avb3 and anti-avb5 integrin antibodies had an effect on the ability of Periostin to mediate cell adhesion in OSCC cells (Kudo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The YH18 motif of βig-h3 mediates the adhesion and growth of aortic VSMCs We have previously reported that the YH18 motif of βig-h3 mediates the adhesion of fibroblasts and endothelial cells through interaction with the αvβ5 and αvβ3 integrins, respectively Nam et al, 2003). In this regard, we investigated a protein motif(s) responsible for the adhesion of aortic VSMCs to βig-h3.…”
Section: Resultsmentioning
confidence: 99%
“…βig-h3 consists of four Fas-1 domains, which are designated as D-I, D-II, D-III, and D-IV domain Nam et al, 2003). Each domain has two conserved Fas-1 regions known as H1 and H2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesion-To assess the involvement of ␤3 and ␤1 integrins in the observed IGF-IR phosphorylation, we applied neutralizing anti-␤3 and anti-␤1 antibodies that were shown before to prevent interaction of fibronectin with the corresponding integrins (24,25). The fibronectin-induced increase in phosphorylation of IGF-IR was abolished in cells cultured on fibronectin in the presence of the ␤3 blocking antibody (Fig.…”
Section: ␤3 Integrin Mediates the Fibronectin-induced Phosphorylationmentioning
confidence: 99%